When Large Employers Come to Town: Labor Market Entry and Corporate Disclosure - Roh, Yongoh (The Accounting Review, 2026)
ABSTRACT This paper examines how incumbent firms adjust their disclosure behavior in response to heightened labor market competition. Using announcements of large employer entries into local labor markets, I find that incumbent firms located in the affected counties increase the disclosure of positive, forward-looking information. This response is concentrated among incumbent firms that compete more directly with entrant firms for similar workers and is strongest in local labor markets where employee retention pressures are likely to be more severe. Additional analyses show that the response extends to qualitative disclosure, particularly job-related and reputation-enhancing press releases, is associated with more favorable subsequent employment outcomes, and is unlikely to be explained by alternative motives related to productivity spillovers, supply-chain linkages, product market competition, or capital market considerations. Overall, the evidence supports the view that firms use public disclosure to shape employee perceptions and mitigate turnover risk when competition for talent intensifies. Data Availability: Data are available from the public and commercial sources cited in the paper. JEL Classifications: M41; D22; J23; J63.